Experimental Study Regarding The Influence Of Compliant Hinges Geometry In Mechanical Structures - Lates, D.; Casvean, Marius (International Journal of Engineering and Management Sciences, 2019)
In this paper an experimental study will be carried out, on the influence of geometry, using different compliant mechanical couplings. In the first part of the paper will be presented the compliance of the couplings and a number of consecrated works on this theme will be quoted. The article continues with the case study made on three types of compliant joints. These joints and the mechanics that substitute them will be presented. Towards the end of the paper we explain the experimental method and its results. The final ideas concerning this work will be filled out by conclusions and research directions.